Microbiological assessment of the chemo-mechanical caries removal - Marković Dejan; Pavlica Dušan; Perić Tamara (Serbian Medical Society - Dental Section, Belgrade, 2003)
The aim of the study was to assess the efficacy of the chemo-mechani- cal method for caries removal based on microbiological analyses of dentine samples. Sixty freshly extracted teeth with coronaly caries were analysed. In the experimental group (30 teeth) chemo-mechanical caries removal was performed, and in the control group (30 teeth) rotary instruments were used. Before the caries treatment and at the completion of cavity preparation dentine samples were taken by sterile round ISO 012 bur for microbiological analyses. Results of the study showed significant differences between initial and final dentine samples, while differences between the experimental and control group were not significant. The microbiological analyses in the present study imply that the chemo-mechanical method for caries removal is as efficient as the conventional technique.